Engineered Nanomaterials and Type I Allergic Hypersensitivity Reactions - Alsaleh, Nasser B.; Brown, Jared M. (Frontiers in Immunology, 2020)
Type I allergic hypersensitivity disorders (atopy) including asthma, atopic dermatitis, allergic rhinitis and food allergy are on the rise in developed and developing countries. Engineered nanomaterials (ENMs) span a large spectrum of material compositions including carbonic, metals, polymers, lipidbased, proteins and peptides and are being utilized in a wide range of industries including healthcare and pharmaceuticals, electronics, construction and food industry, and yet, regulations for the use of ENMs in consumer products are largely lacking. Prior evidence has demonstrated the potential of ENMs to induce and/or aggravate type I allergic hypersensitivity responses. Furthermore, previous studies have shown that ENMs could directly interact with and activate key T-helper 2 (Th2) effector cell types (such as mast cells) and the complement system, which could result in pseudoallergic (nonIgE-mediated) hypersensitivity reactions. Nevertheless, the underlying molecular mechanisms of ENM-mediated induction and/or exacerbation of type I immune responses are poorly understood. In this review, we first highlight key examples of studies that have demonstrated inherent immunomodulatory properties of ENMs in the context of type I allergic hypersensitivity reactions, and most importantly, we attempt to put together the potential molecular mechanisms that could drive ENM-mediated stimulation and/or aggravation of type I allergic hypersensitivity responses.